Carbon intensity of mass timber materials: impacts of sourcing and transportation - Atnoorkar, Swaroop; Ghatpande, Omkar A.; Haile, Selam L.; Goetsch, Heather E.; Harris, Chioke B. (Frontiers in Built Environment, 2024)
Mass timber construction is widely considered a promising alternative construction method to reduce buildings' total life-cycle carbon emissions because wood is a carbon sink. \Ac{clt} panels, manufactured by gluing lumber layers with grains at right angles, are potential low-carbon alternatives to carbon-intensive concrete and steel construction. However, most environmental impact assessment studies do not consider variation in transportation impacts within the \ac{clt} supply chain when calculating life-cycle impacts. This study investigates the embodied primary energy and the \ac{gwp} of \ac{clt} supply chain decisions regarding the type of timber species used, the U.S.\ region it is sourced from, and the location of the \ac{clt} mill. Longer transport distances in the supply chain for timber and \ac{clt} panels can contribute as much as 923 MJ/m2 (20%) of the embodied primary energy of a \ac{clt} building, and the use of a higher-density timber species increases this contribution to 1246 MJ/m2 (24%), with most of that energy derived from fossil energy sources. For perspective, the \ac{gwp} of a building whose \ac{clt} panels and timber have been transported by truck over 6,000 km (252--270 kgCO2/m2) is greater than the \ac{gwp} of an equivalent \ac{rc} building (245 kgCO2/m2). Thus, factors like the location of \ac{clt} processing facilities and the type of timber species can significantly impact the overall life-cycle assessment and, if chosen appropriately, can mitigate the environmental impacts of \ac{clt} construction.